Animal Reproduction (IntechOpen, 2022)
Reproduction is the backbone of animal-based food production. The reproductive systems of animals vary and are species-dependent. In this regard, all terrestrial animals perform internal fertilization, whereas aquatic animals perform different reproductive strategies such as internal fertilization without mating, external fertilization, viviparous, oviparous, and parthenogenesis. Today, reproductive biotechnology is an important part of the conservation and propagation of animals. This book addresses several hot topics in the field of reproduction of terrestrial and aquatic animals. Over five sections and eight chapters, this volume examines subjects such as cryopreservation, embryo transfer, avian reproduction, intraovarian gestation, and more.